The Effectiveness of Android Application as a Student Aid Tool in Understanding Physics Project Assignments (Jurnal Pendidikan IPA Indonesia, 2019)
Indonesian students are addicted to using gadgets, which unfortunately brings negative impacts. Using the gadget for a long duration will undoubtedly affect the quality of students if it is not directed to appropriate and beneficial use. After school, students are preoccupied with their gadgets so that they waste a lot of their time to play games and leave their homework undone. As a result, their interest in doing science assignments are meager. Gadget addiction and the low level of learning interest in carrying out tasks are the new problems in education. Therefore, efforts need to be made to overcome them. This study aims to determine the effectiveness of android application as student aid tools in understanding the task of Physics. The subjects of this research were all VIII graders of SMP Islam Terpadu Arrozaq Rantauprapat. The type of this research is quantitative with a pre-experimental design (one-shot case study). This study directed the students to utilize their gadgets in completing the task of physics. The instruments used in this research were the video-checking rubric and the effectiveness questionnaire. This research has been carried out for three months, and video-checking was carried out at the end of each month after the project assignments were collected. The results of data analysis in this study indicated that the utilization of an android application as a tool of students is considered sufficient. The students become more enthusiastic about working on assignments and accessing the internet through gadgets on positive uses.